Relationship between emotional sphere, tolerance of uncertainty and productive decision-making strategies - Mariya A. Shestova (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
Tolerance for uncertainty is a component of intellectual-personal potential and mediates the decision-making process (DM). The state of Art demonstrates that tolerance of uncertainty contributes to effective and productive decision-making and associated with the constructs that reveal the emotional sphere of a person. The theory of dynamic regulative systems predicts that in the decision-making process, both cognitive and emotional-personal components (tolerance of uncertainty, emotional creativity, and emotional experience of threats from uncertainty) can reach the upper levels of the hierarchy. The role of tolerance for uncertainty in the decision-making processes is relatively well known, however the contribution of the emotional sphere to the problem-solving processes, as well as its relationship with tolerance of uncertainty, is not sufficiently studied. The aim of the study was to establish correlations between emotional creativity and tolerance for uncertainty and productive decision-making strategies. Hypotheses: positive correlation between emotional creativity tolerance of uncertainty productive decision-making strategies was expected. As a result, positive relationship between emotional creativity and tolerance of uncertainty was revealed. It is shown that emotional creativity can be involved in decision-making processes in two ways: to help overcome uncertainty and increase the effectiveness of problem solving, or to lead to difficulties in overcoming interpersonal intolerance of uncertainty, due to a decrease in components of self-control and control of emotional expression. Taken together, the results demonstrate the inclusion of uncertainty tolerance in the emotional sphere of the person, and show the involvement of these components in the DM processes.